From a circle to a sphere: the ultrasound imaging of ovarian follicle with 2D and 3D technology. (4th March 2019) - Re, Claudia; Mignini Renzini, Mario; Rodriguez, Amelia; Dal Canto, Mariabeatrice; Buccheri, Matteo; Sacchi, Sandro; Bartolucci, Silvia; Fadini, Rubens; La Marca, Antonio
Abstract: Ultrasound follicular count (antral follicle count, AFC) is a necessary tool for measuring ovarian reserve, whereby the estimated number of follicles responsive to FSH can predict the number of oocytes retrieved in IVF cycles and may be the basis for individualized ovarian stimulation therapy. Advances in the ultrasound technology have recently lead to the improvement in resolution and quality of the image. Moreover the automatic measurements of follicular diameter by using some specific 3D software seems associated to several advantages when compared to the 2D technique. Examination time is reduced because the ultrasound scan data are stored and can be analyzed in detail at a later time. These data can be reconstructed in any plane, regardless of the original scan plane facilitating the detailed analysis. Another advantage is that this new technique reduces the operator's influence on scan interpretation and objectivity; therefore, interobserver variability is reduced. Using follicular volume obtained with sono AVC as the measure of follicular growth combined with volume-based criteria for the hCG triggering may in the future improve the treatment outcome compared to that achieved with conventional monitoring with follicular diameter. Better knowledge in this area could be helpful to optimize IVF outcome, by refining ovarian stimulation protocols and obtain high quality oocytes.